Dinámica de la vegetación y del banco de semillas en un humedal herbáceo lacustrino (Venezuela) - Gordon, Elizabeth (Universidad de Costa Rica, 2000)
Vegetation and seed banks association with seasonal water depth variations were studied in a herbaceous wetland of a tropical lake in Monagas, Venezuela. The sampling was done in 1 Ox 1 0 m2 quadrates located at random in two zones of the lagoon. In each sampling four quadrates per zone were analyzed for relative species density, species richness, life forms and water depth. Soil samples were taken simultaneously for size and composition of the seed banks (seedling emergence method). Soil pH was five. The organic total fraetion of the soil varied between 38% and 52%, and the conductivity between 1 14 and 1 82 flmhos!cm. 50 species were recorded: 46% perennial herbs, 22% vines, 1 2% suffrutescents and 10% hydrophytes. The highest species richness was recorded during periods of fain and rain-dry transition. Hymenachne amplexicaulis, Leersia hexandra, Sacciolepis striata and Polygonum acuminatum were among the most important species numerically. The total density of seed bank varied between 5689 and 1 3936 seedlings/m2. In the seed bank there were 58 species: 43% perennial herbs, 22% suffrutescents, 12% vines 9% annual herbs and 9%, hydrophytes. The highest species richness in the seed bank was during periods of dry and dry-rain transition. Cyperus odora/us. Eleocharis interstincta, Ludwigia hyssopifolía, L. lithospermifolia and Po/ygonum acuminatum had the highest densities. The potential flora of these wetlands included 76 species, but only 33 (43%) were common lo the seed bank and Ihe vegetation.